2005
DOI: 10.1038/nbt1176
|View full text |Cite
|
Sign up to set email alerts
|

A genetic strategy to treat sickle cell anemia by coregulating globin transgene expression and RNA interference

Abstract: The application of RNA interference (RNAi) to stem cell-based therapies will require highly specific and lineage-restricted gene silencing. Here we show the feasibility and therapeutic potential of coregulating transgene expression and RNAi in hematopoietic stem cells. We encoded promoterless small-hairpin RNA (shRNA) within the intron of a recombinant gamma-globin gene. Expression of both gamma-globin and the lariat-embedded small interfering RNA (siRNA) was induced upon erythroid differentiation, specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 28 publications
1
79
0
2
Order By: Relevance
“…Low VCNs minimize risk of insertional mutagenesis and other side effects of high-level shRNA delivery, 18 such as might have been the delayed differentiation of MEL-HBB IVSI-110(G>A) cells and the increased cell death in primary cultures observed here. To this end, expression of intronic shRNAs under RNApolII promoters can be predicted to avoid the interferon response, 19 but our initial attempts to replicate the corresponding design proposed by Samakoglu et al 20 did not lead to detectable target knockdown (data not shown). Importantly, Brendel et al 21 successfully employed control elements of the GLOBE vector for knockdown of the γ-globin repressor BCL11A.…”
Section: Supplementary Discussionmentioning
confidence: 99%
“…Low VCNs minimize risk of insertional mutagenesis and other side effects of high-level shRNA delivery, 18 such as might have been the delayed differentiation of MEL-HBB IVSI-110(G>A) cells and the increased cell death in primary cultures observed here. To this end, expression of intronic shRNAs under RNApolII promoters can be predicted to avoid the interferon response, 19 but our initial attempts to replicate the corresponding design proposed by Samakoglu et al 20 did not lead to detectable target knockdown (data not shown). Importantly, Brendel et al 21 successfully employed control elements of the GLOBE vector for knockdown of the γ-globin repressor BCL11A.…”
Section: Supplementary Discussionmentioning
confidence: 99%
“…The latter approach has the potential advantage of providing lifelong therapy (assuming transduction is efficient and expression is robust and sustained) but has the associated potential risks of insertional oncogenesis. A recent paper has shown that the coexpression of an shRNA against ␤ S and a ␥-globin transgene had therapeutic benefit in human erythrocytes derived from lentivirally transduced hematopoietic stem cells (21). A drug-like siRNA would require repeated treatments and a strategy for efficient systemic delivery into erythroid precursors.…”
Section: Discussionmentioning
confidence: 99%
“…For genetic function analysis, multi-gene constructs could be used to investigate combinatorial effects, to determine the presence of functional redundancy, or the degree of synergistic or antagonistic interplay between molecular components (Chung et al, 2006;Rao et al, 2006;Xia et al, 2006). In addition, the ability to co-ordinate transgene expression with gene silencing also renders the technology useful for therapeutic applications which may require the silencing (via intronic siRNA) of a faulty gene or allele followed by substitution with a wild-type or functional gene (via exon transgene expression) (Samakoglu et al, 2006). From a practical perspective single multi-expression constructs also possess several useful characteristics compared to multiple individual constructs used either in combination or successively.…”
Section: Discussionmentioning
confidence: 99%